Performance study of the integration between wireless LAN and ATM LAN - Liew, Jing Hong (Faculty of Computer Science and Information Technology, 2005)
Merits of both emerging WLANs and high-speed ATM LANs motivate the integration of these two LANs. Nevertheless, there are various differences between the two LANs. Furthermore, IEEE 802.11b WLANs encounter a problem of bandwidth limitation, where data rates supported are up to only 11 Mbps, compared to 155 Mbps supported by ATM. Therefore, it is a challenge to integrate a WLAN and an ATM LAN. In this research, a PC-based router or multihomed computer is set up to integrate a WLAN and an ATM LAN. Experiments are conducted to investigate the performance, in particular the throughput and video performances, of the integration, and the improve the performance.